Linkage disequilibrium in Huntington's disease: an improved localisation for the gene. - Snell, R G (1989)
The search for the Huntington's disease gene has recently concentrated on the telomere of the short arm of chromosome 4. The evidence suggesting this position has been based on single crossover events, but there is conflicting evidence regarding the position of the gene relative to the most terminal markers. We have found significant linkage disequilibrium between the markers D4S98 (probe BS731B-C) and D4S95 (probe BS674E-D) and HD, which supports a localisation for the gene proximal to D4S90 and makes a telomeric localisation unlikely. This disequilibrium may also prove to be important in the future in allowing modification of risk estimates based on genetic linkage.